PENGARUH IMPLEMENTASI PROGRAM PENGEMBANGAN DIRI TERHADAP HASIL BELAJAR SISWA (Studi Eksperimen Pada Pembelajaran PAI di Kelas V SDN Citapen Kota Tasikmalaya) - Wildan, Asep; Gopar (Program Studi Pendidikan Agama Islam, 2023)
This research is motivated by the implementation of self-development programs in extracurricular activities that have not been implemented optimally. Self-development activities have not received more attention from parents and students themselves. In this study the researchers focused on discussing the implementation of attitude habituation carried out, sincerity, enthusiasm in participating in learning. Student learning outcomes experienced an increase between before treatment or pretest and after treatment or posttest. When compared to the results of the pre-test and post-test values between the experimental class that took part in Islamic self-development activities and those who did not take part, it can be seen that the pretest average value of the class that took part in self-development activities was 41.18 while those who did not took part were 40.59. Meanwhile, the posttest score for the class that took part in self-development activities was 70.59 while those who did not took part were 66.47. Based on the data above, it can be seen that in the experimental class the average student learning outcomes increased by 29.41 and in the control class it increased by 25.88. The results of the calculation of the t test (paired sample t test), indicate that there is a significant difference between the results before and after being given treatment or after participating in an Islamic self-development program. From the SPPS processing data above, it can be seen Sig. (2 tailed) = 0.000 <0.05, then Ho is rejected and Ha is accepted. So it can be concluded that there is an influence of Islamic self-development programs on student learning outcomes